2017
DOI: 10.1016/j.toxlet.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyanobacteria Oscillatoria sp. lipopolysaccharide on B cell activation and Toll-like receptor 4 signaling

Abstract: Cyanobacteria (“blue-green algae”), such as Oscillatoria sp., are a ubiquitous group of bacteria found in freshwater systems worldwide that are linked to illness and in some cases, death among humans and animals. Exposure to cyanobacteria occurs via ingestion of contaminated water or food-products. Exposure of the gut to these bacteria also exposes their toxins, such as lipopolysaccharide (LPS), to B cells in the gut associated lymphoid tissue. However, the effect of Oscillatoria sp. LPS on B cell activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…We observed that ethanol and acetone extracts had an opposite behavior to one another-all ethanol extracts increased the levels of NO produced by RAW 264.7 on their own, suggesting a pro-inflammatory potential ( Figure S1) and thus not meeting the aim of our study. This phenomena could have occurred, at least in part, as a result of the presence of cyanobacteria endotoxins (LPS), as these molecules are more prone to being extracted from more polar solvent mixtures (e.g., ethanol 70% v/v), causing macrophage activation through interactions with Toll-like receptors (TLR4) present in cell membranes [45]. Of the acetone extracts, those of C. issatschenkoi LEGE03282 and C. gracile LEGE12431 also presented pro-inflammatory behavior ( Figure S2), and only three were able to reduce the levels of NO after LPS stimulation ( Figure 2).…”
Section: Anti-inflammatory Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that ethanol and acetone extracts had an opposite behavior to one another-all ethanol extracts increased the levels of NO produced by RAW 264.7 on their own, suggesting a pro-inflammatory potential ( Figure S1) and thus not meeting the aim of our study. This phenomena could have occurred, at least in part, as a result of the presence of cyanobacteria endotoxins (LPS), as these molecules are more prone to being extracted from more polar solvent mixtures (e.g., ethanol 70% v/v), causing macrophage activation through interactions with Toll-like receptors (TLR4) present in cell membranes [45]. Of the acetone extracts, those of C. issatschenkoi LEGE03282 and C. gracile LEGE12431 also presented pro-inflammatory behavior ( Figure S2), and only three were able to reduce the levels of NO after LPS stimulation ( Figure 2).…”
Section: Anti-inflammatory Potentialmentioning
confidence: 99%
“…causing macrophage activation through interactions with Toll-like receptors (TLR4) present in cell membranes [45]. Of the acetone extracts, those of C. issatschenkoi LEGE03282 and C. gracile LEGE12431 also presented pro-inflammatory behavior ( Figure S2), and only three were able to reduce the levels of NO after LPS stimulation (Figure 2).…”
Section: Anti-inflammatory Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In another cadmium project, the role of cadmium in the development of diabetes and diabetic nephropathy was examined. It was shown that cadmium accumulates in the pancreas, increases blood glucose levels, and [26][27][28] From the One Health project focused on cyanobacteria in fresh water, several articles [29][30][31] have documented the effect of cyanobacterium The One Health Initiative has also provided ample opportunities for students to engage in research.…”
Section: History Of Mwu/ccom and Its Tradition Of Researchmentioning
confidence: 99%
“…Toll like receptor (TLR) is a type of inherent immune receptor and may be activated by its ligands, such as lipopolysaccharide (LPS) (8). The downstream signaling pathway consists of recruiting bone marrow myeloid differentiation protein gene 88 (MyD88) and activating the tumor necrosis factor-κB (NF-κB) p65 signaling pathway, which regulates the expression of inflammatory cytokines and promotes the immune response (9,10).…”
Section: Introductionmentioning
confidence: 99%